Effective and Efficient Synchronization in Harmonization of Regulations Indonesia - Syahlan Syahlan (Journal of Human Rights, Culture and Legal System, 2021)
Synchronization and Harmonization of Legislation in Indonesia are carried out by the National Legal Development Agency and the Directorate General of Legislation. The National Legal Development Agency will synchronize and harmonize laws and regulations at the planning stage and drafting the concept of laws and regulations. Meanwhile, the Directorate General of Legislation carries out synchronization and harmonization efforts at the stage of forming the draft legislation. The absence of a definite mechanism regarding the stages of synchronization and harmonization, as well as the separation of the process into two institutions, resulted in the efforts of synchronization and harmonization being not optimal because efforts of synchronization and harmonization are stages that must be carried out in a systemic and integrated manner. This impacts the quality of the laws and regulations produced, which is the goal of synchronization and harmonization. Keywords: Synchronization; Harmonization; Legislation.